American and European Mix Design Approaches Combined: Use of NCHRP Performance Indicators to Analyze Comité Européen de Normalisation Test Results. Issue 1 (January 2014) - Florio, Eugenio; Berti, Carlo; Kasbergen, Cor; Villani, Mirella M.; Scarpas, Athanasios; Erkens, Sandra M. J. G.; Sangiorgi, Cesare; Lantieri, Claudio
This paper describes a project that is part of NL-LAB, a larger, long-term program at Delft University of Technology, Netherlands, which aims to establish the predictive capacity of the current European functional tests for Dutch asphalt concrete (AC) mixtures. In this NL-LAB program, the functional characteristics of resistance to rutting (EN 12697–25), fatigue (EN 12679-24), stiffness (EN 12697–26), and moisture sensitivity (EN 12697-12 and EN 12697–23) are determined for specimens that are (a) mixed and compacted in the lab, (b) mixed in the plant and compacted in the lab, and (c) mixed in the plant and compacted in the road. Eventually, these tests will provide insight into the effect of mixing and compaction on the functional characteristics. The project described in this paper focused on the indirect tensile strength (ITS) and the triaxial cyclic compression test for two AC mixes. The properties found for all three stages of preparation were analyzed with the use of formalistic expressions from the NCHRP Design Guide 1–37A, Level 2, for the estimation of performance indicators. This project aimed to see if these relations remained valid for the Comité Européen de Normalisation tests, especially for mixes with high recycled asphalt pavement content. In the Netherlands, 50% reclaimed asphalt pavement is standard. It was found that the NCHRP Design Guide 1–37A expressions fit the Comité Européen de Normalisation test data quite well for the reclaimed asphalt pavement that contained mixes, especially for the ITS. Currently, another two construction projects are being sampled, and the results will be used to validate and improve the relations.